The influence of stator winding resistance imbalance of an induction motor: evaluation of phase current asymmetry - Prokopenko, S.; Kryvonosov, V.; Kryvonosov, V. (Energy and Automation, 2025)
Asymmetry of the active resistances of stator windings occurs in approximately 30 % of repaired induction motors operating in power complexes of seaports, industrial enterprises, and ships. The resistance asymmetry causes current imbalance in the windings even under symmetrical supply voltage. In a non-symmetrical network, the asymmetry of active resistances can both increase and decrease the current asymmetry coefficient.The use of the Mathcad system enables the calculation of the current asymmetry coefficient depending on the deviation of the supply voltage, variation of stator winding resistances, load current, and supply frequency.Key words: induction motor, active resistance asymmetry, voltage asymmetry, current asymmetry coefficient